2017
DOI: 10.2147/ndt.s136663
|View full text |Cite
|
Sign up to set email alerts
|

Attention–memory training yields behavioral and academic improvements in children diagnosed with attention-deficit hyperactivity disorder comorbid with a learning disorder

Abstract: BackgroundRecent studies have suggested that children with attention-deficit hyperactivity disorder (ADHD) may benefit from computerized cognitive training. Therapy implementation is especially complicated when ADHD is associated with learning disorders (LDs). This study tested the efficacy of a computer-based cognitive training program, namely, computerized cognitive training (CCT), in children with ADHD comorbid with an LD (ADHD-LD), with or without psychostimulant medication.Materials and methodsAfter diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
3
Order By: Relevance
“…More recently, a meta-analysis of cognitive training studies (Karch et al, 2013) revealed favorable effects on secondary measures of outcomes such as behavior, regardless of academic gains. In addition, Farias et al (2017) reported a reduction in both internalizing and externalizing behavior problems following cognitive training with Captain's Log for children with ADHD. Yet, there is extant research with opposing findings.…”
Section: Cognitive Training Effects On Behaviormentioning
confidence: 99%
“…More recently, a meta-analysis of cognitive training studies (Karch et al, 2013) revealed favorable effects on secondary measures of outcomes such as behavior, regardless of academic gains. In addition, Farias et al (2017) reported a reduction in both internalizing and externalizing behavior problems following cognitive training with Captain's Log for children with ADHD. Yet, there is extant research with opposing findings.…”
Section: Cognitive Training Effects On Behaviormentioning
confidence: 99%
“…L'entrainement cognitif pourrait aussi cibler un spectre plus large de fonctions cognitives, notamment sur les plans attentionnel et exécutif (Dentz et al, 2016). Par exemple, le programme Captain's Log Software System comprend 36 exercices répartis en 50 programmes (Farias et al, 2017) et le programme ACTIVATE comprend six jeux ciblant la mémoire de travail, la vitesse de traitement de l'information, l'attention soutenue, l'attention divisée, le raisonnement et l'inhibition (Rosa et al, 2017). Ce type de programmes permettrait de tenir compte de l'hétérogénéité des profils cognitifs associés au TDA/H et d'offrir une prise en charge individualisée.…”
Section: Resultsunclassified
“…La prévalence mondiale du TDA/H est estimée à 5% des enfants d'âge scolaire, ce qui en fait un des troubles neurodéveloppementaux les plus fréquents (Polanczyk, Willcutt, Salum, Hieling et Rohde, 2014). Ce trouble persiste à l'âge adulte dans plus de 50% des cas (Biederman et al, 2006; (Elia, Ambrosini et Berrettini, 2008 ;Farias et al, 2017;Larson, Russ, Kahn et Halfon, 2011). Le TDA/H est aussi le trouble comorbide le plus commun dans le contexte d'un syndrome de Gilles de la Tourette (Rizzo, Gulisano, Calì et Curatolo, 2013).…”
Section: Liste Des Tableauxunclassified
See 1 more Smart Citation
“…In the form of a video game that includes a game of grouping objects, completing signs, remembering and arranging components (Rosa et al, 2017). The same aspect of research conducted by (Farias et al, 2017) The effect of computer-based cognitive rehabilitation interventions on both aspects of attention and working memory, which consists of a combination program of Working Memory, Inhibitory Control, and neurofeedback training in children with AD / HD and subclinical AD / HD. After training, AD / HD symptom severity was reduced in AD / HD and subclinical groups based on interviews with parents (Johnstone et al, 2017).…”
Section: Ct (Cognitive Training) Game -mentioning
confidence: 99%